Creativity and Innovation 4.0. Promoting Renewal through Possibility Thinking - Mangion, Margaret (Farol, 2024)
This article explores the connections between creativity, innovation, and modern citizenship, focusing on “Creativity and Innovation 4.0” to understand how these dimensions contribute to technological advances and reshape social norms. The paper also addresses the challenges and limitations of possibility thinking, including technological inequalities. Finally, the article outlines a path toward a society in which creativity and innovation serve not only economic development but also the enrichment of democratic life.